PEMAKNAAN DAN RESEPSI FUNGSIONAL TRADISI RUTINITAS IDUL FITRI: STUDI LIVING QUR’AN MENGUNJUNGI RUMAH DAN MAKAM ULAMA’ DI DESA KOTO PADANG - Mandala, Ican; Admizal, Iril (LPPM IAIN Sultan Amai Gorontalo, 2023)
The Islamic community's ability to understand the Koran and Hadith has given rise to various forms of understanding with a variety of practices. The response of people in an area to religious practices is often entrenched to the point that it becomes a community tradition. Such as understanding the text of the Koran and Hadith regarding the reception and implementation of practices on the Muslim victory day (Eid al-Fitr). Performing prayers, listening to sermons, visiting graves, gathering and so on decorates Eid al-Fitr in various parts of Indonesia. The practice of interpreting the meaning of Eid al-Fitr in Koto Padang Village is of particular interest in this research, because before the Eid al-Fitr prayers there is a tradition of respecting previous ulama who have made a major contribution to the development of Islamic religious knowledge in this region. This form of attitude of respecting and remembering the cleric is actualized by the community in the practice of visiting and performing sunnah prayers at the cleric's house. Then proceed with prayer or pilgrimage at the cemetery of the cleric named Sheikh Haji Ismail. Interestingly, this tradition is not carried out individually. But it is carried out by the congregation and Eid prayer officers. In the local community's understanding, this phenomenon is a form of interpretation of the Koran and Hadith which is realized in the form of practice. In analyzing the phenomena in this research, field research was used with qualitative methods, living Qur'an and phenomenology approach models. By conducting observations, interviews and documentation as data collection techniques. The aim of this research is an effort to reveal the community's reception and the connection between this tradition and the meaning of certain verses as a basis for implementing this routine tradition. The community's interpretation of this tradition has functional and spiritual values which include acts of respect for ulama, tawassul, friendship, and self-introspection (remembering death).